A New Electrode Design for Direct Bladder Wall Stimulation: A Pilot Minipig Study with Chronic Testing - James Walter; Ioan Hutu; Berndt Tomancok; Alin Adrian Cumpanas; Razvan Bardan; Silviu Latcu; Andrei Rusmir; Dorin Novacescu; Ovidiu Georgescu; Marius Pentea; Andrei Dragos Cumpanas; Helmut Madersbacher (Applied Sciences, 2022)
(1) Aims: To test a newly designed helical-wire hook electrode implanted in the bladder wall to induce contraction and promote voiding. (2) Methods: In three minipigs with a created lesion of the sacral spinal cord, four electrodes were implanted in the bladder wall, ventral to the trigone. Stimulation tests were conducted initially in conscious pigs, and later after general anesthesia. (3) Results: Electrical stimulation in the conscious animals on postoperative days 4 and 7 at 40 Hz was limited to 10 mA, because of abdominal, leg, and anal contractions with animal discomfort; bladder contractions were not induced. Electrical stimulation on postoperative days 9 and 28 at 60 mA under anesthesia induced sustained vesical wall contractions with bladder pressure variations, but without voiding. Simultaneous abdominal contractions occurred, with strong leg and anal contractions. Subsequent stimulation with a single set of electrodes or at 20 Hz induced less vesical pressure response. At autopsy, the electrodes had not migrated, and extraction forces were high, at 7.9 ± 0.9 Newtons (n = 12). (4) Conclusions: Our 28-day study has confirmed the utility of the new electrode design, preventing migration from the bladder wall and making it suitable for long-term electrode implants.